A Novel Hybrid Full Adder using 13 Transistors - Shing Jie, Lee; Ruslan, Siti Hawa (International Journal of Integrated Engineering, 2016)
Full adder is a basic and vital building block for various arithmetic circuits such as multipliers. In this paper, a hybrid 1-bit full adder using complementary metal-oxide semiconductor (CMOS) logic style had been designed. This hybrid adder divided into three modules. Module I is a three transistors XOR gate. Module II is a novel sum circuit which successfully modified with the usage of lesser number of transistors used. Module III is a carry circuit which uses the carry output of module I and several other input to generate carry output. Performance parameters such as power and delay were compared to some of the existing designs. With a 1.8V voltage supply, the average power consumption of proposed hybrid adder was found extremely low which is 2.09 Î¼W and a very low delay of 350 ps. Design in both speed and energy consumption becomes even more significant as the word length of the adder increases. The full adder design is simulated using Tanner EDA version 16 using General Process Design Kit (GPDK) 250nm technology CMOS processes.